Management effectiveness and efficiency of healthcare delivery system at ophthalmology outpatient department (OPD) in the Sadar Hospital, Chuadanga, Bangladesh - Ali, M Idris; Khatun, Monira; Mamun, Abdullah Al; Sharif, Md Mofazzal; Haque, AKM Enamul (KYAMC Journal, 2018)
Background: This present study was carried out in the Outpatient Department of Ophthalmology in Chuadanga Sadar hospital, Bangladesh with the general objective to observe the management effectiveness and efficiency of health service provided in Outpatient Department at Sadar hospital (District level) in Bangladesh and ultimately reveal the need of a managerial personnel in health management other than doctor. Objectives: The objective of the study was to find out management effectiveness, efficiency of health care service at OPD and ultimately reveal need for a managerial personnel for management other than doctor. Materials & Methods: This cross-sectional study was carried out among 450 respondents by using a pre-tested questionnaire over a period of six months. Results: Regarding health care delivery system at outpatient in Bangladesh it was found that before appointment, majority of the respondent (94.44%) were referred to the OPD by local village doctor. After arrival at OPD, majority (29.56%) respondents experienced poor courtesy of the attending personnel. Consultation started between 16-30 minutes after appointment. During consultation with the doctor 66.22% respondents had enough time to consult to a doctor but to some extent. In most (50%) of the cases, consultation time was less than 5 minutes. Most of the respondents (48.88%) were not satisfied with the existing health care. Management effectiveness and efficiency of the existing healthcare service rated as fair (28.44%), poor (24.22%), good (21.57%), very good (13.77%) according to the opinion of the respondents. Ultimately 65.12% respondents sought for a need managerial personnel other than doctor. Conclusion: This study finding concluded need for managerial personnel for hospital management other than doctor himself. KYAMC Journal Vol. 9, No.-2, July 2018, Page 76-80